體育師資培育研究在《教學與教師教育》中之定位：2001-2010 Locating Research on Physical Education Teacher Education in the Teaching and Teacher Education From 2001 to 2010 - 體育師資培育研究在《教學與教師教育》中之定 2001-2010 Locating Research on Physical Education Teacher Education in the Teaching and Teacher Education From 2001 to 2010 (National Taiwan Normal University, 2016)
自1990 年代被宣告為一門研究領域以來，師資培育始終呈現出一種多元學科而非孤立的領域樣貌。可是，究竟體育師資培育在整個師資培育領域中被放在什麼位置上呢？本研究即是為了回應這個提問而書寫的，目的在於瞭解體育師資培育研究的現況，以及10 年內它在整個師資培育知識圈內的定位與趨勢。研究資料為2001-2010 年間發表於《教學與教師教育》期刊的853 篇研究論文，並以發表年代、教師生涯階段、研究議題及研究方法論為構面，採取量化內容分析法將之進行歸納。結果證實，體育師資培育研究正處於師資培育領域中合法的但邊緣的地位，文末將針對此種現象的涵義以及未來體育師資培育研究的建議進行討論。 Teacher education has been considered multidisciplinary since it first became a field of inquiry in the 1990s. However, the relationship between physical education teacher education (PETE) and the larger field of teacher education remains undefined. To determine this relationship, this study aimed to understand the status quo of research on PETE (R-PETE) and its relationship with and trends within the broader knowledge base of teacher education during one decade. A total of 853 studies published in Teaching and Teacher Education from 2001 to 2010 were collected then, applying the method of quantitative content analysis, categorized by publication year, teacher's stages of life career, research issues, and research methodologies. The results confirmed that R-PETE was considered as having a legitimate but peripheral relationship with the larger teacher education field during the study period. This paper discusses the implications of this relationship found and provides recommendations for future research on PETE.